Behaviour of basalt fibre reinforced polymer strengthened timber laminates under tensile loading. (15th June 2016) - Fernando, D.; Frangi, A.; Kobel, P.
Highlights: An experimental, numerical and analytical study on BFRP strengthened timber laminates under tensile loading is presented. Effects of BFRP strengthening on timber laminates with defects are clearly demonstrated. Abstract: Timber has been widely used all over the world as a structural material. The defects such as knots could significantly reduce the mechanical properties of timber, thus significantly affecting the performance of timber structures. Existing studies have demonstrated the ability to use fibre reinforced polymer (FRP) composites to increase the strength, stiffness and the ductility of glulam beams. Such strengthening however, often becomes uneconomical due to higher FRP material volume and the use of expensive FRPs such as carbon FRP and glass FRP. Oppose to current approaches of strengthening glulam beams using FRPs, use of minimal amount of FRPs to reinforce weaker sections, thus reducing the variability and resulting in a higher load carrying capacity, may provide better economical solutions. In addition, the use of cost effective FRPs such as basalt FRP could further reduce the costs. This paper presents an experimental and theoretical investigation aimed at understanding the behaviour of BFRP-strengthened timber sections. The experimental component of the study presented consists of 54 tensile specimens with and without BFRP. In some of the specimens, holes were cut in the mid span to simulate a defect. The experimental study showed that BFRP increases both the strength and stiffness of the timber specimens. Findings of an FE study of BFRP-strengthened timber specimens are also presented. Stress and strain distributions of the specimens, obtained from the FE study are presented and discussed. Based on the findings of the FE study, and idealized strain distribution is presented. This idealized strain distribution was then used to develop analytical models for an equivalent elastic modulus of the regions with defects. In addition, analytical models are also presented to predict the ultimate load carrying capacity of the pure timber and BFRP-strengthened timber specimens. The predictions agreed well with the experimental results. The analytical models were then used in Monte Carlo simulations to demonstrate the effectiveness of the BFRP strengthening. It was found that BFRP could yield significant benefits in terms of increasing the strength and stiffness for the timber sections with defects.